Acetylation modulates LC3 stability and cargo recognition. Issue 4 (22nd January 2019) - Song, Tingting; Su, Haifeng; Yin, Wei; Wang, Liming; Huang, Rui
Abstract : LC3 is a key autophagy‐related protein involved in both autophagosome formation and autophagy cargo recruitment. Despite these functions being exerted by deacetylated LC3, this protein is more abundantly distributed in its acetylated form. Here, we reveal that the stability and cargo recognition ability of LC3 are highly dependent on its acetylation. Through detecting the diffusion rate of soluble LC3 by fluorescence recovery after photobleaching (FRAP), we found that nutrient‐state‐related acetylation inhibited LC3 complex formation. Acetylation blocked LC3's interaction with p62, the autophagic cargo receptor, preventing the mis‐targeting of p62 to nonautophagic LC3 and thus permitting the efficient degradation of autophagic cargoes. Acetylation also inhibited LC3 proteasome‐dependent degradation, thus maintaining LC3 as a long‐lived protein that could serve as a reserve. Altogether, acetylated LC3, the nonactivated form, is suitable for storage and avoids inopportune interactions with other proteins, assuring autophagic degradation. Abstract :